2018
DOI: 10.1007/s00432-018-2643-3
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacokinetics and pharmacodynamics equivalence trial of the proposed pegfilgrastim biosimilar, MYL-1401H, versus reference pegfilgrastim

Abstract: MYL-1401H demonstrated similar PK, PD, and safety to reference pegfilgrastim in healthy volunteers and may be an equivalent option for the prevention of febrile neutropenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 18 publications
7
25
0
Order By: Relevance
“…Robust and correlative PK/PD studies are sensitive at detecting subtle differences in biosimilar efficacy. Previous PK/PD analysis of MYL-1401H demonstrated equivalence with reference pegfilgrastim [ 18 ], consistent with efficacy data from this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Robust and correlative PK/PD studies are sensitive at detecting subtle differences in biosimilar efficacy. Previous PK/PD analysis of MYL-1401H demonstrated equivalence with reference pegfilgrastim [ 18 ], consistent with efficacy data from this study.…”
Section: Discussionsupporting
confidence: 89%
“…Pegfilgrastim was approved in 2002 for CIN prophylaxis, and significant research has gone into pegfilgrastim biosimilar development [ 3 ]. Recent preclinical and PK/PD data have supported biosimilarity between originator pegfilgrastim (Neulasta®; Amgen Inc., Thousand Oaks, CA) and the proposed biosimilar MYL-1401H [ 18 ]. Here, we present data from a phase 3 efficacy and safety trial conducted to confirm equivalence of MYL-1401H with European Union (EU)–sourced reference pegfilgrastim for CIN prophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, the FDA approved the first pegfilgrastim biosimilars, pegfilgrastim-jmdb and pegfilgrastim-cbqv, for the same indications as pegfilgrastim based on data showing highly similar pharmacokinetics, pharmacodynamics, and safety in healthy volunteers. 10,12,[40][41][42][43][44] Pegfilgrastim-jmdb has been shown to have high analytical and functional similarity to pegfilgrastim, with similar structure, molecular mass, physicochemical characteristics, and G-CSF receptor binding affinity. 45,46 A phase I randomized equivalence trial concluded that pegfilgrastim-jmdb demonstrated similar pharmacokinetics, pharmacodynamics, and safety to pegfilgrastim in healthy volunteers.…”
Section: Filgrastim-aafimentioning
confidence: 99%
“…45,46 A phase I randomized equivalence trial concluded that pegfilgrastim-jmdb demonstrated similar pharmacokinetics, pharmacodynamics, and safety to pegfilgrastim in healthy volunteers. 40 In a multicenter randomized phase III efficacy and safety trial, patients with breast cancer receiving myelosuppressive chemotherapy with pegfilgrastim-jmdb support showed no difference in duration of severe neutropenia, time to absolute neutrophil count (ANC) nadir, duration of postnadir recovery, or treatment-related adverse events compared with patients receiving reference pegfilgrastim. 47 Pegfilgrastim-jmdb has also demonstrated low immunogenic potential in healthy volunteers and patients with cancer receiving myelosuppressive chemotherapy.…”
Section: Filgrastim-aafimentioning
confidence: 99%
“…This includes published Phase I studies demonstrating similar PK/PD, safety, and immunogenicity between reference biologic and Cinfa Biotech biosimilar pegfilgrastim (B12019/Pelmeg), 26,27 Accord Healthcare biosimilar pegfilgrastim (INTP5/Pelgraz), 28,29 and Mylan biosimilar pegfilgrastim (MYL-1401H/Fulphila). 30 Crossover designs were used to compare the biosimilar of pegfilgrastim to both EU-and US-reference biologics. 29 In summary, the primary objectives of this study were met, as PK and PD biosimilarity of Sandoz biosimilar pegfilgrastim with USand EU-reference biologics was achieved.…”
Section: Discussionmentioning
confidence: 99%